1996
DOI: 10.1016/0008-6363(96)00028-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarct size is smaller in dogs with pacing-induced heart failure

Abstract: Infarct size produced by a standardized ischemia-reperfusion protocol was smaller in dogs with pacing-induced HF. The reduced extent of infarction could not be attributed to differences in collateral blood flow or the size of the region at risk. Although the hearts in HF dogs were dilated, LV systolic blood pressure and the strength of contraction were lower than controls potentially reducing myocardial oxygen demand and explaining the smaller infarct size in HF dogs. Other mechanisms, however, cannot be disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our findings that CHF cells have improved ischemia tolerance are corroborated by the results of Hoskins et al (15) showing that dogs with pacing-induced failing heart had much smaller infarcts than control animals after ischemia-reperfusion. Thus, despite different pathological stimuli (pacing vs. postinfarction heart failure) and different biological levels (whole heart vs. isolated cardiomyocytes), these two studies show the same phenomenon of better ischemic tolerance of failing myocardium.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings that CHF cells have improved ischemia tolerance are corroborated by the results of Hoskins et al (15) showing that dogs with pacing-induced failing heart had much smaller infarcts than control animals after ischemia-reperfusion. Thus, despite different pathological stimuli (pacing vs. postinfarction heart failure) and different biological levels (whole heart vs. isolated cardiomyocytes), these two studies show the same phenomenon of better ischemic tolerance of failing myocardium.…”
Section: Discussionsupporting
confidence: 89%
“…There is little doubt that ischemia becomes much more arrhythmogenic in the failing heart, in humans and in animal models (Chakko et al 1989; Bril, Forest, and Gout 1991). When infarct size in the nonpreconditioned heart is measured, there are studies that show decreased (Hoskins et al 1996) or unaltered infarct size (Miki et al 2000) in heart failure, depending on the experimental model.…”
Section: Physiologic and Pathologic States Of Altered Ischemic Tolerancementioning
confidence: 99%
“…DeVan and colleagues demonstrated that traditional cardiovascular risk factors, such as advanced age, are associated with a greater magnitude and delayed recovery from endothelial IR-injury in humans 3 . Also experimental studies suggest that the presence of cardiovascular risk factors or disease is associated with exaggerated IR-injury 2,4,5 , although some studies suggest otherwise 6,7 . Accordingly, we examined the hypothesis that HF patients demonstrate an increased endothelial IR-injury compared to healthy peers in vivo.…”
Section: Introductionmentioning
confidence: 99%